LA PLANIFICACION DIDACTICA Y SU INCIDENCIA EN EL PROCESO DE ENSEÑANZA APRENDIZAJE, EN LOS ALUMNOS DE NOVENO AÑO DE EDUCACION BASICA DEL COLEGIO TECNICO SALECIANO " SAN RAFAEL" DE LA CIUDAD DE ESMERALDA DURANTE ELPERIODO LECTIVO 2004-2005. - BEATRIZ. I. BASTIDAS.B (2006)
TEACHING PLANNING AND ITS IMPACT ON THE TEACHING AND LEARNING PROCESS, IN THE STUDENTS OF THE NINTH YEAR OF BASIC EDUCATION OF THE SALECIANO "SAN RAFAEL" TECHNICAL SCHOOL OF THE CITY OF ESMERALDA DURING THE 2004-2005 SCHOOL PERIOD.